2017
DOI: 10.1007/s00394-017-1421-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations between dietary patterns, socio-demographic factors and anthropometric measurements in adult New Zealanders: an analysis of data from the 2008/09 New Zealand Adult Nutrition Survey

Abstract: A 'Healthy' dietary pattern was associated with higher socio-economic status and reduced adiposity, while the 'traditional' pattern was associated with lower socio-economic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
48
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 38 publications
12
48
1
1
Order By: Relevance
“…The results of the second analysis indicate that gender is the social determinant with the largest effect on mean differences in food group consumption. Many works have shown that gender is associated with food habits [13,14,[16][17][18]52,54,58], and, as we indicated in the Introduction section, women usually exhibit better food habits than their male counterparts [13,14,[16][17][18]. In the case of male students, our study shows they have a higher intake of dairy products, olives, nuts and seeds, red meat and processed meat, sweets, eggs, alcoholic drinks and fast food.…”
Section: Discussionsupporting
confidence: 62%
“…The results of the second analysis indicate that gender is the social determinant with the largest effect on mean differences in food group consumption. Many works have shown that gender is associated with food habits [13,14,[16][17][18]52,54,58], and, as we indicated in the Introduction section, women usually exhibit better food habits than their male counterparts [13,14,[16][17][18]. In the case of male students, our study shows they have a higher intake of dairy products, olives, nuts and seeds, red meat and processed meat, sweets, eggs, alcoholic drinks and fast food.…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, the Western dietary pattern was significantly associated with a higher BMI, WHR, SBP, DBP, TG, TC and FBG concentrations. These findings are in accordance with previous studies that report an inverse association between a prudent/healthy dietary pattern and BMI, WC and WHR (49)(50)(51) . It has also been observed that adherence to a prudent/healthy dietary pattern was associated with lower smoking habits (52) .…”
Section: Discussionsupporting
confidence: 93%
“…Fourth, dietary patterns explained 15.7% of the total eating pattern variability in this study. This was similar to that reported in other studies (45,46). Finally, although socioeconomic factors associated with anemia, such as annual income and education level, were used in a previous study (39), these factors were not investigated in the 2010-2015 NHNS.…”
Section: Discussionsupporting
confidence: 77%